(untitled) (Research, Society and Development, 2022)
The objective is to evaluate the profile of patients with autism spectrum disorder (ASD) treated in the Discipline of Dental Care for Patients with Special Needs (SNP) of the Dentistry School of Federal University of Rio Grande do Sul (UFRGS). From the dental records of patients treated at an outpatient level between 2001 and 2019, information was obtained regarding the patient’s age at the first visit, gender, form of access, systemic condition of the patient with ASD, continuous use of medication and treatment received on their last visit to the clinic. The data were tabulated in an Excel® spreadsheet and analyzed based on the percentage value. It was found that the ASD represented 6,4% of the SNPs attended in the discipline, with 75,3% male with a median age of 19,56 years coming from Porto Alegre. Of these patients, 78,3% were taking medication, the most frequent being: antipsychotics (60,8%), anticonvulsants (39.2%), antidepressants (12,4%) and anxiolytics (11,3%). The most frequent treatments performed in the last clinical visit were prevention (36%), periodontal (17,5%), dentistry (14,4%) and surgery (13,4%). We conclude that it is important for dentists to be aware of the systemic and associated conditions of patients with ASD as highlighted, which are also linked to the use of medications and to have pharmacological knowledge, so that they can safely serve them in clinical practice, considering that there is a probability of oral and systemic manifestations with the use of these drugs, in addition to their adverse reactions.